2005
DOI: 10.1002/cne.20452
|View full text |Cite
|
Sign up to set email alerts
|

Neural control mechanisms of the pheromone‐triggered programmed behavior in male silkmoths revealed by double‐labeling of descending interneurons and a motor neuron

Abstract: Male silkmoths, Bombyx mori, exhibit a characteristic zigzagging behavior consisting of straight-line walking, zigzagging turns, and looping. The timing for shifting the turning direction is synchronized to the sideways head movements controlled by neck motor neurons (NMNs) including a cervical ventral NMN (cv1-NMN). It has been suggested that this programmed behavior is instructed by two types of activity patterns descending from the brain and the thoracic ganglion: one is a phasic excitation and the other is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 26 publications
4
72
0
1
Order By: Relevance
“…Speculation of the neural mechanisms and pathways underlying dynamic use of optic flow during the pheromonetriggered behavioural response Earlier studies on the neural mechanism underlying pheromonetriggered behavioural responses have demonstrated that surge and zigzagging are controlled by two different neural circuits (Kanzaki, 2004;Wada and Kanzaki, 2005). Neural activity during surge shows a phasic response in a descending motor pathway, whereas zigzagging shows so-called 'flip-flop' activity, which is a longlasting tonic response generated by the premotor centre of the silkmoth's brain (Iwano et al, 2010;Wada and Kanzaki, 2005).…”
Section: Differences Between Responses To Open-loop and Biased Closedmentioning
confidence: 99%
See 2 more Smart Citations
“…Speculation of the neural mechanisms and pathways underlying dynamic use of optic flow during the pheromonetriggered behavioural response Earlier studies on the neural mechanism underlying pheromonetriggered behavioural responses have demonstrated that surge and zigzagging are controlled by two different neural circuits (Kanzaki, 2004;Wada and Kanzaki, 2005). Neural activity during surge shows a phasic response in a descending motor pathway, whereas zigzagging shows so-called 'flip-flop' activity, which is a longlasting tonic response generated by the premotor centre of the silkmoth's brain (Iwano et al, 2010;Wada and Kanzaki, 2005).…”
Section: Differences Between Responses To Open-loop and Biased Closedmentioning
confidence: 99%
“…When the silkmoth detects an additional pheromone cue, this behavioural sequence restarts from the beginning (Kanzaki, 1996;Kanzaki, 1998;Kanzaki et al, 1992). Previous neurophysiological studies on this pheromone-triggered behaviour have demonstrated that two neural circuits control behaviour during surge and zigzagging and that the loop is presumably a part of zigzagging and controlled by the same neural circuit (Kanzaki, 1996;Kanzaki, 2004;Wada and Kanzaki, 2005). Hence, from now on, we will discuss behaviour during surge and zigzagging only.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For simplicity, we omit the phase of straight-line walking from the target. This simplification is supported by [26], which indicated that the neural circuit for straightline walking and that for zigzag turning and looping are di erent. The right and left inputs in Fig.…”
Section: Target Sequential Patternmentioning
confidence: 88%
“…The activity of these, so called, flip/flop neurons is directly correlated with the body orientation and zigzagging of the moth while tracing a pheromone trail. Moreover, the orientation switches appear to be caused by the difference of pheromone concentration in the anteanne (Olberg 1993;Mishima & Kanzak 1998;Wada & Kanzaki 2005). Therefore, olfactory stereo information is used in our model to trigger the orientation changes whenever the sensor reading difference of two chemo-sensors is above threshold (Fig.…”
Section: A Moth Neural Based Localization Strategymentioning
confidence: 99%